Hubungan Cita Rasa dan Kepuasan Pelayanan terhadap Sisa Makanan Santri di Pondok Pesantren - Widya Nuryana; Dian Ayu Ainun Nafies; Lilia Faridatul Fauziah; Miftahul Munir (Inovasi Kesehatan Global, 2026)
Food waste is an important indicator in evaluating the effectiveness of food service management, especially in institutional settings such as Islamic boarding schools. High levels of food waste can be influenced by several factors, including food taste and satisfaction with food service. This study aimed to analyze the relationship between food taste and food service satisfaction with food waste among students at Al-Hasyimi Islamic Boarding School Sukolilo Bancar. This research used a quantitative method with a cross-sectional design. The population consisted of 127 female students, with 98 respondents selected using stratified random sampling. Data were collected using the Comstock form to measure food waste and questionnaires to assess food taste and food service satisfaction. Data analysis was conducted using univariate and bivariate analysis with the Spearman Correlation test. The results showed a significant relationship between food taste and food waste (p=0.000), as well as between food service satisfaction and food waste (p=0.000).